2005
DOI: 10.1081/cnv-200058813
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activation of Peritoneal Macrophages by Thymosin Alpha-1

Abstract: It was been previously reported that thya1 can be used to activate monocytes, BMDM and TAM. However, the effect of thya1 on other tissue macrophages has not been investigated. Moreover, there is no report about the use of thya1-treated macrophages in adoptive immunotherapy of cancer. In view of these observations in the present study, we checked the response of various tissue macrophages to thya1 for activation. Tissue macrophages showed differential response to thya1; moreover, adoptive transfer of peritoneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…An impressive amount of data reported by Shrivastava and his colleagues reveal the benefits of Ta1 to TAM-targeted cancer therapy. [114][115][116][117] They showed that Ta1 prompted the production of IL-1, TNF, reactive oxygen intermediates and NO in TAMs 114,116 and induced M1 TAMs and in turn prolonged the survival time of mice with Dalton lymphoma. 116,117 Finally, we would note the effects of re-polarized TAMs on adaptive immunity.…”
Section: Enhancing M1 Tumoricidal Activity Of Tamsmentioning
confidence: 99%
“…An impressive amount of data reported by Shrivastava and his colleagues reveal the benefits of Ta1 to TAM-targeted cancer therapy. [114][115][116][117] They showed that Ta1 prompted the production of IL-1, TNF, reactive oxygen intermediates and NO in TAMs 114,116 and induced M1 TAMs and in turn prolonged the survival time of mice with Dalton lymphoma. 116,117 Finally, we would note the effects of re-polarized TAMs on adaptive immunity.…”
Section: Enhancing M1 Tumoricidal Activity Of Tamsmentioning
confidence: 99%
“…32 As shown by other research groups, the relation between T␣1 and cancer is complex and based also on the direct effect of T␣1 on various immune effector cell types, among which are macrophages and DCs. 9,[33][34][35] As an example, Shrivastava et al have shown that T␣1 activates monocytes, bone marrow-derived macrophages (BMDMs) and tumor-associated macrophages to a tumoricidal state. 33 This effect occurs via the enhancement of their production of macrophageactivating cytokines and other molecules (i.e., IL-1, tumor necrosis factor (TNF), reactive oxygen intermediates (ROI), and nitric oxide (NO)), which act in autocrine manner, with consequent increased pinocytosis, phagocytosis, antigen presentation, and tumor cytotoxicity by these important effector cells.…”
Section: Action On Immune Effector Cellsmentioning
confidence: 99%
“…33 This effect occurs via the enhancement of their production of macrophageactivating cytokines and other molecules (i.e., IL-1, tumor necrosis factor (TNF), reactive oxygen intermediates (ROI), and nitric oxide (NO)), which act in autocrine manner, with consequent increased pinocytosis, phagocytosis, antigen presentation, and tumor cytotoxicity by these important effector cells. 33,34 Peng et al have shown that T␣1 induces the production of IL-6, IL-10, and IL-12 in murine BMDMs through IB kinase (IKK) and mitogen-activated protein kinases (MAPK) pathways. 35 Romani et al have shown that T␣1 upregulates the expression of Toll-like receptor (TLR) 2, 5, 8, and 9 and protects mice from challenge by invasive aspergillosis in a myeloid differentiate factor 88 (MyD88)-dependent way.…”
Section: Action On Immune Effector Cellsmentioning
confidence: 99%
“…15 The recent finding that granulopoiesis and lymphopoiesis in bone marrow are specifically and reciprocally coupled by inflammation 38 makes the control of inflammation a central issue in transplantation. Although T␣1 activates innate cells, including DCs, to an antimicrobial 16 and antitumor state, 39 the attenuation of the immunogenic/inflammatory activity of myeloid DCs by T␣1 through IDO induction qualifies T␣1 as a unique immunoregulatory molecule capable of fine-tuning and controlling the quality of the immune response, which may result in the control of inflammatory response and restoration of protective antimicrobial immunity in the relative absence of GVHD, as seen in mice that received transplants. As chronic inflammation may be linked to cancer development, T␣1 would be expected to work in conditions in which prolonged inflammation may promote cancer.…”
Section: Thymosin ␣1 Activates Ido In Dendritic Cells 2271mentioning
confidence: 99%